Catalyst for oxidation and method for preparing and using same and method for oxidation of durene

CN117942964BActive Publication Date: 2026-10-30CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211319841.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-26
Publication Date
2026-10-30
Estimated Expiration
2042-10-26

AI Technical Summary

Technical Problem

[0004]本发明的目的是为了克服现有技术气相氧化时目标产物收率不高的问题,提供一种氧化用催化剂及其制备方法和应用以及制备均酐的方法,该催化剂有利于反应过程中分子的传质和吸附,提高了催化剂的选择性和效率,例如在用于制备均酐中具有均酐收率高的优势

Benefits of technology

[0013]与现有技术相比,本发明催化剂改善了催化效率,提高了催化剂的活性和稳定性。例如采用本发明催化剂用于均四甲苯氧化制均酐时,均酐收率最高可达到89.5%,取得了较好的技术效果。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application relates to the technical field of catalyst preparation, and discloses a catalyst for oxidation, a preparation method and application of the catalyst and a method for oxidizing durene. The catalyst comprises a carrier and an active component, the active component comprises titanium dioxide and an active element for oxidation, and the mesopore volume proportion of the active component is 1-10%. The preparation method of the catalyst comprises the following steps: (1) mixing a solution containing an active element source for oxidation, oxidized titanium and a titanium precursor to obtain an active component precursor; and (2) contacting the active component precursor with the carrier, and then performing calcination to obtain the catalyst. The catalyst improves the efficiency of the active element for oxidation and improves the activity of the catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of catalyst preparation technology, specifically to an oxidation catalyst, its preparation method and application, and a method for the oxidation of mesitylene. Background Technology

[0002] Methoxylene is a crucial component of heavy aromatics produced as a byproduct in large-scale ethylene plants, catalytic reforming units, aromatics plants, disproportionation, and isomerization processes, making its efficient utilization extremely important. Currently, methoxylene is primarily used to prepare pyromellitic dianhydride (pyromellitic anhydride), which is then widely used as a high-value-added chemical intermediate. Its most significant application is in the synthesis of polyimide materials, which can be applied in cutting-edge technology fields such as aerospace and electronics. The main method for producing pyromellitic anhydride from methoxylene is the gas-phase oxidation process. This process offers advantages such as one-step reaction to generate pyromellitic anhydride, a simple process flow, and ease of automation and continuous production. However, this process suffers from disadvantages such as generally low pyromellitic anhydride yield with solid catalysts and low production efficiency.

[0003] US5001100 discloses a catalyst for the production of homogenate, and CN107715900 discloses a multi-component, low-vanadium catalyst for the gas-phase oxidation method to prepare pyromellitic dianhydride. Because the gas-phase oxidation process is a complex heterogeneous catalytic process, the above methods involve various side reactions, resulting in very low homogenate yields. Therefore, the currently used catalysts suffer from low efficiency and low homogenate yields. Summary of the Invention

[0004] The purpose of this invention is to overcome the problem of low yield of target product during gas-phase oxidation in the prior art, and to provide an oxidation catalyst, its preparation method and application, as well as a method for preparing homogeneous anhydride. This catalyst is beneficial to the mass transfer and adsorption of molecules during the reaction process, and improves the selectivity and efficiency of the catalyst. For example, it has the advantage of high homogeneous anhydride yield in the preparation of homogeneous anhydride.

[0005] To achieve the above objectives, the first aspect of the present invention provides an oxidation catalyst comprising a support and an active component, wherein the active component comprises titanium dioxide and oxides of active oxidation elements; wherein the mesoporous volume fraction of the active component is 1-10%.

[0006] The second aspect of the present invention provides a method for preparing the catalyst of the present invention, the method comprising: (1) mixing a solution containing an active element source for oxidation with titanium oxide and a titanium precursor to obtain an active component precursor; (2) contacting the active component precursor with a support, and then calcining it to obtain the catalyst;

[0007] Preferably, the raw materials for preparing the titanium precursor include: a titanium source, an organic modifier, and a solvent.

[0008] A third aspect of the present invention provides the application of the catalyst described herein in the oxidation reaction of methyl-containing aromatic hydrocarbons.

[0009] A fourth aspect of the present invention provides a method for the gas-phase oxidation of mesitylene, the method comprising: reacting mesitylene, air and the catalyst described herein under gas-phase oxidation conditions.

[0010] Preferably, the reaction conditions include: a reaction temperature of 330-500°C; and / or

[0011] Volumetric hourly space velocity is 2000-10000 h⁻¹ -1 ;

[0012] The mass concentration of mesitylene is 13-60 g / m³. 3 .

[0013] Compared with existing technologies, the catalyst of this invention improves catalytic efficiency and enhances its activity and stability. For example, when using the catalyst of this invention for the oxidation of mesitylene to homohydric anhydride, the homohydric anhydride yield can reach up to 89.5%, achieving good technical results. Detailed Implementation

[0014] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0015] The first aspect of this invention provides an oxidation catalyst comprising a support and an active component, wherein the active component comprises titanium oxide and oxides of active oxidation elements; wherein the mesoporous volume fraction of the active component is 1%-10%. Compared with the prior art, the catalyst of this invention improves catalytic efficiency and enhances the activity and stability of the catalyst.

[0016] In this invention, titanium dioxide and the active element for oxidation in the catalyst interact, while the mesoporous volume ratio of the active component is controlled to be 1%-10%. When this catalyst is used in the oxidation reaction of methyl-containing aromatic hydrocarbons, especially in the oxidation of mesitylene to homohydric anhydride, the yield of the target product can be significantly improved. The inventors speculate that this is because the appropriate mesoporous ratio improves the catalyst's contact efficiency while reducing the occurrence of deep oxidation side reactions.

[0017] According to a preferred embodiment of the present invention, the mesoporous volume fraction of the active component is 1%-8% (e.g., 1%, 1.2%, 3%, 4.5%, 6%, 7%, 7.2%, or 8%). Using the aforementioned embodiment, the yield of anhydride can be further homogenized.

[0018] In this invention, "mesopore volume of active component" refers to the ratio of the volume of mesopores of active component on the surface of inert support in catalyst to the total pore volume, wherein 2-50 nm is called mesopore or mesopore.

[0019] In this invention, the active mesopore volume ratio is obtained by low-temperature nitrogen physical adsorption, which is a conventional method for analyzing and characterizing catalyst pore volume.

[0020] According to a preferred embodiment of the present invention, the titanium dioxide contains 80-100 wt% anatase titanium dioxide. By adopting the aforementioned preferred embodiment, the interaction between active component species can be further increased, which promotes catalyst activity, optimizes catalyst performance, effectively improves the selectivity of the target product, and thus increases the yield of the target product.

[0021] According to a preferred embodiment of the present invention, in the catalyst, the mass ratio of titanium to active element for oxidation is (0.01-55):1, preferably (0.05-25):1, for example 0.05:1, 1:1, 1.5:1, 1.7:1, 2:1, 3:1, 4:1, 6:1, 10:1, 15:1 or 20:1.

[0022] The active elements for oxidation described in this invention include main catalytic active elements and co-catalytic active elements.

[0023] According to a particularly preferred embodiment of the present invention, the mass ratio of the main catalytic active element to the co-catalytic active element is 1:(0.01-1), preferably 1:(0.01-0.2), for example 1:0.01, 1:0.05, 1:0.06, 1:0.1, 1:0.15 or 1:0.2.

[0024] According to a particularly preferred embodiment of the present invention, the main catalytically active element includes vanadium. By adopting the aforementioned preferred embodiment, the activity-promoting effect of the active component on the catalyst can be enhanced, thereby increasing the yield of the target product.

[0025] According to a preferred embodiment of the present invention, the mass ratio of vanadium to titanium oxide is 1:(0.01-50), more preferably 1:(0.08-20), for example 1:0.08, 1:0.1, 1:1.5, 1:1.7, 1:1.8, 1:2, 1:5, 1:8, 1:12, 1:15, 1:18, or 1:20. By adopting the aforementioned preferred embodiment, the yield of homogenizing anhydride can be further improved.

[0026] According to a preferred embodiment of the present invention, the co-catalytic active element includes co-catalytic component A and co-catalytic component B; co-catalytic component A includes transition metal elements and / or alkali metal elements, and co-catalytic component B includes non-metallic elements. By adopting the aforementioned preferred embodiment, it is beneficial to improve the redox capability of the catalyst, thereby better increasing the yield of the target product.

[0027] In this invention, unless otherwise specified, the content and ratio of active components in the catalyst are based on the amount of feed.

[0028] In this invention, as long as the objective of this invention can be achieved, there are no special requirements for the mass ratio of the co-catalytic active element to the main catalytic active element. According to a preferred embodiment of this invention, the mass ratio of the co-catalytic component A to vanadium is (0.001-0.5):1, and the mass ratio of the co-catalytic component B to vanadium is (0.001-0.5):1, for example, 0.001:1, 0.005:1, 0.01:1, 0.03:1, 0.05:1, 0.08:1, 0.1:1, 0.2:1, 0.3:1, 0.4:1, or 0.5:1.

[0029] In this invention, unless otherwise specified, the ratios between the active components in the catalyst refer to elemental ratios.

[0030] According to a preferred embodiment of the present invention, the mass ratio of the co-catalytic component A to vanadium is (0.005-0.1):1; the mass ratio of the co-catalytic component B to vanadium is (0.005-0.1):1, for example, 0.001:1, 0.005:1, 0.02:1, 0.04:1, 0.05:1, 0.08:1, 0.1:1, 0.2:1, 0.3:1, 0.4:1, or 0.5:1. By adopting the aforementioned preferred scheme, the synergistic effect between the active components can be further improved, thereby increasing the yield of the target product.

[0031] In this invention, the co-catalytic component A can be any conventional choice in the art, as long as it achieves the objective of the invention. According to a preferred embodiment of the invention, the co-catalytic component A is selected from one or more elements selected from niobium, tantalum, molybdenum, tungsten, silver, neodymium, potassium, sodium, rubidium, cerium, and chromium. By adopting the aforementioned preferred embodiment, the oxidation capacity of the catalyst can be further improved, thereby increasing the yield of the target product.

[0032] In this invention, the co-catalytic component B can be any conventional choice in the art, as long as it achieves the objective of the invention. According to a preferred embodiment of the invention, the co-catalytic component B includes one or more nonmetals from Group IIIA, Group IVA, and Group V. Using the aforementioned embodiments can better optimize catalyst performance and improve the selectivity of homogenized anhydride.

[0033] According to a particularly preferred embodiment of the present invention, the co-catalytic component B comprises one or more of boron, phosphorus, and tellurium. By employing the aforementioned preferred embodiment, the adsorption performance of the catalyst for oxygen can be further improved.

[0034] In this invention, as long as the objective of this invention can be achieved, there are no special requirements for the mass ratio of the active component to the support. According to a preferred embodiment of this invention, the mass ratio of the active component to the support, calculated as oxide, is 1:(1-50), preferably 1:(4-25). By adopting the aforementioned preferred scheme, the interaction between the active component and the support can be further improved, and the ability of the catalyst surface to chemically adsorb oxygen during the oxidation of mesitylene can be further increased.

[0035] According to a preferred embodiment of the present invention, the carrier is an inert carrier selected from one or more of α-Al2O3, silicon carbide and ceramic rings.

[0036] In this invention, catalysts with the aforementioned characteristics can achieve the purpose of this invention. There are no special requirements for the preparation method of the catalyst. The second aspect of this invention provides a preparation method of the catalyst comprising: (1) mixing a solution containing an active element source for oxidation with titanium oxide and a titanium precursor to obtain an active component precursor; (2) contacting the active component precursor with a support and then calcining it to obtain the catalyst.

[0037] In this invention, titanium oxide and titanium precursor work together to provide titanium oxide active components for the catalyst. At the same time, the catalyst obtained by the interaction of the specific titanium oxide active components with the active elements containing oxidation has better oxygen adsorption and oxidation capabilities.

[0038] According to a preferred embodiment of the present invention, the raw materials for preparing the titanium precursor include: a titanium source, an organic modifier, and a solvent. By adopting the aforementioned preferred embodiment, the mesoporous volume ratio of the catalyst active component can be controlled, and the interaction with titanium oxide and the active element containing oxidation can be regulated.

[0039] In this invention, as long as the objective of the invention can be achieved, there are no particular requirements for the mass ratio of titanium oxide to titanium precursor. According to a preferred embodiment of the invention, based on the mass of titanium oxide provided, the mass ratio of titanium oxide to titanium precursor is (0.001-50):1, preferably (0.01-10):1, for example 0.01:1, 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, or 10:1. By adopting the aforementioned preferred scheme, the synergistic effect with titanium oxide can be further improved, and the interaction with the active element containing oxidation can be strengthened.

[0040] In this invention, the titanium source can be any conventional choice in the art as long as it can achieve the purpose of this invention. According to a preferred embodiment of this invention, the titanium source includes at least one of titanate, titanium alkoxide, titanium nitrate, titanium halide, and titanium sulfate; preferably, the titanium source is selected from at least one of tetraisopropyl titanate, tetrabutyl titanate, titanium nitrate, titanium chloride, and titanium sulfate.

[0041] According to a preferred embodiment of the present invention, the titanium oxide comprises anatase titanium oxide; preferably, the content of anatase titanium oxide in the titanium oxide is greater than or equal to 80 wt%, more preferably greater than or equal to 90 wt%. Anatase titanium oxide is used as an example to illustrate the advantages of the present invention, but the present invention is not limited thereto.

[0042] In this invention, as long as the purpose of this invention can be achieved, there are no special requirements for the preparation method of the titanium precursor. According to a preferred embodiment of this invention, the preparation method of the titanium precursor includes: mixing and contacting a titanium source and an organic modifier in a solvent under conditions of pH 0.1-6, followed by filtration, separation, washing, and drying.

[0043] In this invention, as long as the objective of the invention can be achieved, there are no special requirements for the mixing and contact conditions. According to a preferred embodiment of the invention, the contact conditions in the preparation method of the titanium precursor include: a temperature of 20-150°C, preferably 30-90°C; a pH of 0.5-3; and a time of 0.5-5 hours. By adopting the aforementioned preferred scheme, the oxidation activity of the catalyst can be further improved.

[0044] According to a preferred embodiment of the present invention, the washing method described in the preparation method of the titanium precursor is a conventional method in the art, which can be achieved by washing with water until neutral. The present invention will not elaborate on this further.

[0045] According to a preferred embodiment of the present invention, the drying method described in the preparation method of the titanium precursor is a commonly used method in the art, and there are no special limitations on the drying temperature and time, for example, the drying time is 0.5-5h.

[0046] In this invention, as long as the objective of this invention can be achieved, there are no special requirements for the mass ratio of the titanium source to the organic modifier. According to a preferred embodiment of this invention, the mass ratio of the titanium source to the organic modifier is (0.001-100):1, preferably (0.01-10):1, for example 0.01:1, 0.5:1, 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1 or 10:1.

[0047] In this invention, as long as the objective of this invention can be achieved, there are no special requirements for the mass ratio of titanium source to solvent. As long as the titanium source and organic modifier can be fully mixed in the solvent, it is acceptable. According to a preferred embodiment of this invention, the mass ratio of titanium source to solvent is (0.001-100):1, preferably (0.01-10):1, for example 0.01:1, 0.5:1, 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1 or 10:1.

[0048] In this invention, there are no particular limitations on the solvent used in the preparation method of the titanium precursor, as long as the titanium source and the organic modifier can be fully mixed in the solvent. According to a preferred embodiment of this invention, the solvent is selected from one or more of C1-C4 alcohols (e.g., methanol, ethanol, propanol or n-butanol), polyethanolamines (e.g., diethanolamine or triethanolamine) and water.

[0049] In the embodiments of the present invention, a preferred embodiment of the present invention is described using ethanol and water in a volume ratio of 1:(1-5) as solvents, but the present invention is not limited thereto.

[0050] In this invention, the organic modifier can be any conventional choice in the art as long as it can achieve the purpose of this invention. According to a preferred embodiment of this invention, the organic modifier includes one or more of organic amine compounds, organic alcohol compounds, polymers and anionic surfactants.

[0051] According to a preferred embodiment of the present invention, the organic modifier is selected from one or more of dodecylamine, hexadecylammonium bromide, hexadecyltrimethylammonium bromide, polyethylene glycol, dextrin, triblock copolymer P123, and sodium dodecyl sulfate.

[0052] According to a preferred embodiment of the present invention, the organic modifier is selected from one or more of dodecylamine, hexadecyltrimethylammonium bromide and triblock copolymer P123;

[0053] According to a particular embodiment of the present invention, the organic modifier is a mixture of triblock copolymer P123 and hexadecyltrimethylammonium bromide, preferably in a mass ratio of (0.01-10):1.

[0054] According to a preferred embodiment of the present invention, the preparation of a solution containing an active element source for oxidation includes: mixing and contacting a main catalytic active element source and a reducing agent in an aqueous solution to obtain a mixed solution, and then adding a co-catalytic active element source and mixing.

[0055] According to a preferred embodiment of the present invention, the mass ratio of the main catalytic active element source to the reducing agent is (0.001-10):1.

[0056] In the preparation of the solution containing the active element source for oxidation in this invention, the amount of the aqueous solution is only required to ensure that the main catalytic active element source and the reducing agent are fully mixed and contacted. This invention does not impose any special restrictions on it. According to a preferred embodiment of this invention, the mass ratio of the aqueous solution to the main catalytic active element source is (1-100):1.

[0057] In this invention, the type of main catalytic active element source can be selected as needed. According to a preferred embodiment of this invention, the main catalytic active element source includes a vanadium source.

[0058] In this invention, the vanadium source can be any conventional choice in the art as long as it achieves the purpose of this invention. According to a preferred embodiment of this invention, the vanadium source is selected from at least one of vanadium nitrate, vanadium(III) sulfate, vanadium oxalate, vanadium(IV) sulfate hydrate, vanadium sulfate, vanadium trichlorooxide, potassium metavanadate, ammonium metavanadate, sodium metavanadate, sodium orthovanadate, vanadium diacetylacetone oxide, vanadium triisopropoxylate, vanadium n-butoxide, vanadium acetylacetone, vanadium acetylacetone oxide, vanadium trichloride, vanadium tetrachloride, vanadium trichloride, triethylvanadium oxide, and vanadium pentoxide.

[0059] In this invention, the type and amount of co-catalytic active element source can be selected as needed, and there are no special limitations on this. According to some preferred embodiments of this invention, the co-catalytic active element source includes co-catalytic active source A to provide co-catalytic component A and co-catalytic active source B to provide co-catalytic component B. The selection can be made according to the type and amount of the active component of the desired catalyst. Examples of co-catalytic active source A include silver nitrate, sodium nitrate, ammonium molybdate, ammonium tungstate, potassium nitrate, and cerium nitrate. Examples of co-catalytic active source B include boric acid and telluric acid, but this invention is not limited to these.

[0060] According to a preferred embodiment of the present invention, the reducing agent includes one or more of formic acid, oxalic acid, citric acid and L-ascorbic acid.

[0061] In the preparation of the solution containing the active element source for oxidation, there are no special restrictions on the mixing contact conditions as long as the purpose of thorough mixing can be achieved. According to a preferred embodiment of the present invention, the mixing contact temperature in the preparation of the solution containing the active source is 40-120°C.

[0062] In this invention, as long as the objective of this invention can be achieved, the contact method between the solution containing the active source and the carrier, according to a preferred embodiment of this invention, is either spraying or immersion.

[0063] According to a preferred embodiment of the present invention, when using the spraying method, the spraying conditions include: a spraying temperature of 80-200°C, preferably 100-150°C.

[0064] According to a preferred embodiment of the present invention, when the impregnation method is used, the impregnation conditions include an impregnation temperature of 80-200°C, preferably 80-150°C.

[0065] In this invention, the calcination conditions in the catalyst preparation method can be conventionally selected in the art, and this invention does not have any special restrictions on them. According to a preferred embodiment of this invention, the calcination conditions include: a calcination temperature of 400-700℃ and a calcination time of 1-6 hours, preferably 3-5 hours.

[0066] This invention provides the application of the catalyst described in this invention or the catalyst prepared by the preparation method of this invention in the oxidation reaction of aromatic hydrocarbons containing methyl groups and in gas-phase oxidation reactions.

[0067] In this invention, it is understood that methyl-containing aromatic hydrocarbons refer to compounds formed by replacing one or more hydrogen atoms in an aromatic hydrocarbon with methyl groups. According to a preferred embodiment of this invention, the aromatic hydrocarbon is selected from one or more of toluene, o-xylene, mesitylene, methylnaphthalene, 2,3-dimethylnaphthalene, and 2,3,6,7-tetramethylnaphthalene.

[0068] Another aspect of the present invention provides a method for the gas-phase oxidation of mesitylene, the method comprising: reacting mesitylene, air and the catalyst described in the present invention or the catalyst prepared by the preparation method of the present invention under gas-phase oxidation conditions;

[0069] According to a preferred embodiment of the present invention, the reaction conditions further include: a reaction temperature of 330-500°C and a volume hourly space velocity of 2000-10000 h⁻¹. -1 4000-6000h is preferred -1 The mass concentration of mesitylene is 13-60 g / m³. 3 Preferred concentration: 16-35g / m 3 .

[0070] In this invention, "volume hourly space velocity" refers to the volume hourly space velocity of a mixture of mesitylene and air; "mass concentration of mesitylene" refers to the mass concentration of mesitylene in air.

[0071] The gas-phase oxidation method of mesitylene described in this invention does not have special requirements for the reaction pressure; for example, the reaction can be carried out at atmospheric pressure.

[0072] The present invention will be described in detail below through embodiments, including comparative examples:

[0073] Yield = (mass of anhydride produced / mass of mesitylene added) * 100%.

[0074] Example 1

[0075] 110g of triblock copolymer P123 was added to 250ml of ethanol aqueous solution with a volume ratio of 1:3. The pH was adjusted to 1.5 with sulfuric acid. 300g of titanium sulfate was added at 40℃, and the pH was adjusted to maintain at 1.5. The reaction was carried out for 2h. The reactants were filtered, washed, and dried for 2h to obtain the titanium precursor.

[0076] 100g of oxalic acid and 450ml of distilled water were placed in a flask, stirred, and heated to 85℃. After the oxalic acid was completely dissolved, an oxalic acid solution was prepared. 86g of ammonium metavanadate was added to the prepared oxalic acid solution and stirring was continued to obtain an ammonium oxalate oxyvanadate solution. 3g of silver nitrate and 4g of boric acid were added to the solution. 80g of titanium dioxide and 45g of titanium precursor were weighed and added to the solution, and stirring was continued to obtain a catalyst precursor. The catalyst precursor was loaded into a spraying machine, sprayed at 120℃, and uniformly sprayed onto an α-Al2O3 support. The substrate was then placed in a muffle furnace and calcined at 560℃ for 5 hours. After natural cooling, the catalyst was obtained.

[0077] The mass ratio of the active component to the support in the catalyst is 1:20; the active component of the catalyst is characterized by pore volume analysis, and its mesoporous volume accounts for 1.2%; the titanium dioxide in the catalyst contains 85 wt% anatase titanium dioxide.

[0078] Using mesitylene and air as raw materials, a fixed-bed reactor was used to evaluate the gas-phase oxidation reaction of mesitylene in the presence of a catalyst. The reaction conditions were 400 °C, atmospheric pressure, and a gas hourly space velocity (GHSV) of 3500 h⁻¹. -1 Raw material feed concentration 17g / m³ 3 The average anhydride yield was measured to be 87.8%.

[0079] Example 2

[0080] 110g of hexadecyltrimethylammonium bromide was added to 250ml of an ethanol-water solution with a volume ratio of 1:3. The pH was adjusted to 1.5 with sulfuric acid. 300g of tetrabutyl titanate was added at 40℃, and the pH was adjusted to maintain at 1.5. The reaction was carried out for 2 hours. The reactants were filtered, washed, and dried for 2 hours to obtain the titanium precursor.

[0081] 100g of oxalic acid and 450ml of distilled water were placed in a flask, stirred, and heated to 85℃. After the oxalic acid was completely dissolved, an oxalic acid solution was prepared. 86g of ammonium metavanadate was added to the prepared oxalic acid solution and stirring was continued to obtain an ammonium oxalate oxyvanadate solution. 3g of silver nitrate and 4g of boric acid were added to the solution. 80g of titanium dioxide and 45g of titanium precursor were weighed and added to the solution, and stirring was continued to obtain a catalyst precursor. The catalyst precursor was loaded into a spraying machine, sprayed at 120℃, and uniformly sprayed onto an α-Al2O3 support. The substrate was then placed in a muffle furnace and calcined at 560℃ for 5 hours. After natural cooling, the catalyst was obtained.

[0082] The mass ratio of the active component to the support in the catalyst is 1:20; the active component of the catalyst is characterized by pore volume analysis, and its mesoporous volume accounts for 3.3%; the titanium dioxide in the catalyst contains 85 wt% anatase titanium dioxide.

[0083] The gas-phase oxidation reaction conditions for mesitylene were the same as in Example 1, and the yield of the homogeneous anhydride was measured to be 88.2%.

[0084] Example 3

[0085] 110g of dodecylamine was added to 250ml of ethanol-water solution with a volume ratio of 1:3. The pH was adjusted to 1.5 with sulfuric acid. 360g of tetraisopropyl titanate was added at 40℃. The pH was adjusted to maintain at 1.5. The reaction was carried out for 2 hours. The reactants were filtered, washed, and dried for 2 hours to obtain the titanium precursor.

[0086] 100g of oxalic acid and 450ml of distilled water were placed in a flask, stirred, and heated to 85℃. After the oxalic acid was completely dissolved, an oxalic acid solution was prepared. 86g of ammonium metavanadate was added to the prepared oxalic acid solution and stirring was continued to obtain an ammonium oxalate oxyvanadate solution. 5g of silver nitrate, 3g of sodium nitrate, and 4g of boric acid were added to the solution. 80g of titanium dioxide and 45g of titanium precursor were weighed and added to the solution, and stirring was continued to obtain a catalyst precursor. The catalyst precursor was loaded into a spraying machine, sprayed at 120℃, and uniformly sprayed onto an α-Al2O3 support. The substrate was then placed in a muffle furnace and calcined at 560℃ for 5 hours. After natural cooling, the catalyst was obtained.

[0087] The mass ratio of the active component to the support in the catalyst is 1:20; the active component of the catalyst is characterized by pore volume analysis, and its mesoporous volume accounts for 4.5%; the titanium dioxide in the catalyst contains 85 wt% anatase titanium dioxide.

[0088] The gas-phase oxidation reaction conditions for mesitylene were the same as in Example 1, and the yield of the homogeneous anhydride was measured to be 88.7%.

[0089] Example 4

[0090] 110g of triblock copolymer P123 was added to 250ml of ethanol aqueous solution with a volume ratio of 1:3. The pH was adjusted to 1.5 with sulfuric acid. 300g of titanium sulfate was added at 80℃, and the pH was adjusted to maintain at 1.5. The reaction was carried out for 2h. The reactants were filtered, washed, and dried for 2h to obtain the titanium precursor.

[0091] 100g of oxalic acid and 450ml of distilled water were placed in a flask, stirred, and heated to 85℃. After the oxalic acid was completely dissolved, an oxalic acid solution was prepared. 86g of ammonium metavanadate was added to the prepared oxalic acid solution and stirring was continued to obtain an ammonium oxalate oxyvanadate solution. 3g of ammonium molybdate and 7g of telluric acid were added to the solution. 80g of titanium dioxide and 45g of titanium precursor were weighed and added to the solution, and stirring was continued to obtain a catalyst precursor. The catalyst precursor was loaded into a spraying machine, sprayed at 120℃, and uniformly sprayed onto an α-Al2O3 support. The substrate was then placed in a muffle furnace and calcined at 560℃ for 5 hours. After natural cooling, the catalyst was obtained.

[0092] The mass ratio of the active component to the support in the catalyst is 1:20. The active component of the catalyst was characterized by pore volume analysis, and its mesoporous volume accounted for 5.8%. The titanium dioxide in the catalyst contains 85 wt% anatase titanium dioxide.

[0093] The gas-phase oxidation reaction conditions for mesitylene were the same as in Example 1, and the yield of the homogeneous anhydride was measured to be 89.5%.

[0094] Example 5

[0095] 110g of triblock copolymer P123 was added to 250ml of ethanol aqueous solution with a volume ratio of 1:3. The pH was adjusted to 1.5 with sulfuric acid. 300g of titanium sulfate was added at 40℃ and the pH was adjusted to maintain at 1.5. The reaction was carried out for 8h. The reactants were filtered, washed and dried for 2h to obtain the titanium precursor.

[0096] 100g of oxalic acid and 450ml of distilled water were placed in a flask, stirred, and heated to 85℃. After the oxalic acid was completely dissolved, an oxalic acid solution was prepared. 86g of ammonium metavanadate was added to the prepared oxalic acid solution, and stirring was continued to obtain an ammonium oxalate oxyvanadate solution. 7g of ammonium tungstate and 4g of telluric acid were added to the solution. 80g of titanium dioxide and 45g of titanium precursor were weighed and added to the solution, and stirring was continued to obtain a catalyst precursor. The catalyst precursor was loaded into a spraying machine, sprayed at 120℃, and uniformly sprayed onto an α-Al₂O₃ support. The substrate was then placed in a muffle furnace and calcined at 560℃ for 5 hours. After natural cooling, the catalyst was obtained.

[0097] The mass ratio of the active component to the support in the catalyst is 1:20; the active component of the catalyst was characterized by pore volume analysis, and its mesoporous volume ratio was 6.6%; the titanium dioxide in the catalyst contains 85 wt% anatase titanium dioxide.

[0098] The gas-phase oxidation reaction conditions for mesitylene were the same as in Example 1, and the yield of the homogeneous anhydride was measured to be 88.3%.

[0099] Example 6

[0100] 110g of triblock copolymer P123 was added to 250ml of ethanol aqueous solution with a volume ratio of 1:3. The pH was adjusted to 0.5 with sulfuric acid. 300g of titanium sulfate was added at 40℃, and the pH was adjusted to maintain at 0.5. The reaction was carried out for 8h. The reactants were filtered, washed, and dried for 2h to obtain the titanium precursor.

[0101] 100g of oxalic acid and 450ml of distilled water were placed in a flask, stirred, and heated to 85℃. After the oxalic acid was completely dissolved, an oxalic acid solution was prepared. 86g of ammonium metavanadate was added to the prepared oxalic acid solution, and stirring was continued to obtain an ammonium oxalate oxyvanadate solution. 3g of potassium nitrate and 5g of boric acid were added to the solution. 80g of titanium dioxide and 45g of titanium precursor were weighed and added to the solution, and stirring was continued to obtain a catalyst precursor. The precursor was loaded into a spraying machine and sprayed uniformly onto an α-Al₂O₃ support at a spraying temperature of 120℃. The substrate was placed in a muffle furnace and calcined at 560℃ for 5 hours. After natural cooling, the catalyst was obtained.

[0102] The mass ratio of the active component to the support in the catalyst is 1:20; the active component of the catalyst is characterized by pore volume analysis, and its mesoporous volume accounts for 7.2%; the titanium dioxide in the catalyst contains 85 wt% anatase titanium dioxide.

[0103] The gas-phase oxidation reaction conditions for mesitylene were the same as in Example 1, and the yield of the homogeneous anhydride was measured to be 87.5%.

[0104] Example 7

[0105] 180g of triblock copolymer P123 was added to 250ml of ethanol aqueous solution with a volume ratio of 1:3. The pH was adjusted to 1.5 with sulfuric acid. 300g of titanium sulfate was added at 40℃, and the pH was adjusted to maintain at 1.5. The reaction was carried out for 2h. The reactants were filtered, washed, and dried for 2h to obtain the titanium precursor.

[0106] 100g of oxalic acid and 450ml of distilled water were placed in a flask, stirred, and heated to 85℃. After the oxalic acid was completely dissolved, an oxalic acid solution was prepared. 86g of ammonium metavanadate was added to the prepared oxalic acid solution, and stirring was continued to obtain an ammonium oxalate oxyvanadate solution. 7g of cerium nitrate and 4g of boric acid were added to the solution. 80g of titanium dioxide and 45g of titanium precursor were weighed and added to the solution, and stirring was continued to obtain a catalyst precursor. The catalyst precursor was loaded into a spraying machine and sprayed uniformly onto an α-Al₂O₃ support at a spraying temperature of 120℃. The substrate was placed in a muffle furnace and calcined at 560℃ for 5 hours. After natural cooling, the catalyst was obtained.

[0107] The mass ratio of the active component to the support in the catalyst is 1:20; the active component of the catalyst is characterized by pore volume analysis, and its mesoporous volume accounts for 6.8%; the titanium dioxide in the catalyst contains 85 wt% anatase titanium dioxide.

[0108] The gas-phase oxidation reaction conditions for mesitylene were the same as in Example 1, and the yield of the homogeneous anhydride was measured to be 88.4%.

[0109] Example 8

[0110] Following the method of Example 1, 110g of triblock copolymer P123 was replaced with 55g of triblock copolymer P123 and 55g of cetyltrimethylammonium bromide, and other conditions were the same as in Example 1.

[0111] The mass ratio of the active component to the support in the catalyst is 1:20; the active component of the catalyst is characterized by pore volume analysis, and its mesoporous volume accounts for 3.5%; the titanium dioxide in the catalyst contains 85 wt% anatase titanium dioxide.

[0112] The gas-phase oxidation reaction conditions for mesitylene were the same as in Example 1, and the yield of the homogeneous anhydride was measured to be 90.1%.

[0113] Example 9

[0114] Following the method of Example 1, instead of weighing 80g of titanium dioxide and 45g of titanium precursor and adding them to the solution, weigh 0.8g of titanium dioxide and 124.2g of titanium precursor and add them to the solution, with other conditions the same as in Example 1.

[0115] The mass ratio of the active component to the support in the catalyst is 1:20. The active component of the catalyst was characterized by pore volume analysis, and its mesoporous volume accounted for 7.9%. The titanium dioxide in the catalyst contains 75 wt% anatase titanium dioxide.

[0116] The gas-phase oxidation reaction conditions for mesitylene were the same as in Example 1, and the yield of the homogeneous anhydride was measured to be 86.7%.

[0117] Example 10

[0118] Following the method of Example 1, instead of weighing 80g of titanium dioxide and 45g of titanium precursor and adding them to the solution, weigh 123g of titanium dioxide and 2g of titanium precursor and add them to the solution, with other conditions the same as in Example 1.

[0119] The mass ratio of the active component to the support in the catalyst is 1:20. The active component of the catalyst was characterized by pore volume analysis, and its mesoporous volume ratio was 1.3%; the titanium dioxide in the catalyst contains 100 wt% anatase titanium dioxide.

[0120] The gas-phase oxidation reaction conditions for mesitylene were the same as in Example 1, and the yield of the homogeneous anhydride was measured to be 85.9%.

[0121] Example 11

[0122] Following the method of Example 1, the pH was adjusted to be maintained at 5 during the preparation of the titanium precursor, and other conditions were the same as in Example 1.

[0123] The active components of the catalyst were characterized by pore volume analysis, and the mesoporous volume ratio was 8.8%; the titanium dioxide in the catalyst contained 85 wt% anatase titanium dioxide.

[0124] The gas-phase oxidation reaction conditions for mesitylene were the same as in Example 1, and the yield of the homogeneous anhydride was measured to be 85.1%.

[0125] Comparative Example 1

[0126] Add 300g of titanium sulfate to 250ml of water, adjust the pH to maintain it at 1.5, react at 80℃ for 2h, filter and separate the reactants, wash them, and dry them for 2h to obtain the titanium precursor.

[0127] 100g of oxalic acid and 450ml of distilled water were placed in a flask, stirred, and heated to 85℃. After the oxalic acid was completely dissolved, an oxalic acid solution was prepared. 86g of ammonium metavanadate was added to the prepared oxalic acid solution, and stirring was continued to obtain an ammonium oxalate oxyvanadate solution. 3g of silver nitrate and 4g of boric acid were added to the solution. 80g of titanium dioxide and 45g of titanium precursor were weighed and added to the solution, and stirring was continued to obtain a catalyst precursor. The precursor was loaded into a spraying machine and sprayed uniformly onto an α-Al₂O₃ support at a spraying temperature of 120℃. The substrate was placed in a muffle furnace and calcined at 560℃ for 5 hours. After natural cooling, the catalyst was obtained.

[0128] The mass ratio of the active catalyst component to the support was 1:20. The active catalyst component was characterized by pore volume analysis, and its mesoporous volume fraction was 0.13%.

[0129] The gas-phase oxidation reaction conditions for mesitylene were the same as in Example 1, and the yield of the homogeneous anhydride was measured to be 80.9%.

[0130] Comparative Example 2

[0131] Following the method of Example 1, instead of weighing 80g of titanium dioxide and 45g of titanium precursor and adding them to the solution, weigh 125g of titanium precursor (prepared according to the method of Example 1) and add it to the solution, with the other conditions being the same as in Example 1.

[0132] The active components of the catalyst were characterized by pore volume analysis, and the mesoporous volume ratio was 13.2%; the titanium dioxide in the catalyst contained 85 wt% anatase titanium dioxide.

[0133] The gas-phase oxidation reaction conditions for mesitylene were the same as in Example 1, and the yield of the homogeneous anhydride was measured to be 79.2%.

[0134] Comparative Example 3

[0135] Following the method of Example 1, instead of weighing 80g of titanium dioxide and 45g of titanium precursor and adding them to the solution, 125g of titanium dioxide was weighed and added to the solution, with the same conditions as in Example 1.

[0136] The active components of the catalyst were characterized by pore volume analysis, and the mesoporous volume ratio was 0.5%; the titanium dioxide in the catalyst contained 85 wt% anatase titanium dioxide.

[0137] The gas-phase oxidation reaction conditions for mesitylene were the same as in Example 1, and the yield of the homogeneous anhydride was measured to be 81.2%.

[0138] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.

Claims

1. A method for preparing an oxidation catalyst, characterized in that, The method includes: (1) mixing a solution containing an active element source for oxidation with titanium dioxide and a titanium precursor to obtain an active component precursor; (2) The active component precursor is contacted with the support, and then calcined to obtain the catalyst for oxidation; The mass ratio of the titanium oxide to the titanium precursor is (0.001-50):1, based on the mass of titanium oxide provided. The preparation method of the titanium precursor includes: mixing and contacting the titanium source and the organic modifier in a solvent under conditions of pH 0.1-6, followed by filtration, separation, washing, and drying; The organic modifier is selected from one or more of dodecylamine, hexadecylammonium bromide, hexadecyltrimethylammonium bromide, polyethylene glycol, dextrin, triblock copolymer P123, and sodium dodecyl sulfate; The mass ratio of the titanium source to the organic modifier is (0.001-100):1; The catalyst comprises a support and an active component, wherein the active component includes titanium oxide and oxides of active elements for oxidation; wherein the mesoporous volume fraction of the active component is 1-10%; The carrier is selected from one or more of α-Al2O3, silicon carbide, and ceramic rings; The active elements for oxidation include main catalytic active elements and co-catalytic active elements; The main catalytically active element includes vanadium; The co-catalytic active elements include co-catalytic component A and co-catalytic component B; The co-catalytic component A is selected from one or more of niobium, tantalum, molybdenum, tungsten, silver, neodymium, potassium, sodium, rubidium, cerium and chromium; The co-catalytic component B includes one or more of boron, phosphorus, and tellurium.

2. The preparation method according to claim 1, wherein, The titanium oxide contains 80-100 wt% anatase titanium oxide; and / or In the catalyst, the mass ratio of titanium to active element for oxidation is (0.01-55):

1.

3. The preparation method according to claim 2, wherein, In the catalyst, the mass ratio of titanium to active elements for oxidation is (0.05-25):

1.

4. The preparation method according to claim 1, wherein, The mass ratio of the main catalytic active element to the co-catalytic active element is 1:(0.01-1).

5. The preparation method according to claim 1, wherein, The mass ratio of the main catalytic active element to the co-catalytic active element is 1:(0.01-0.2); and / or The mass ratio of vanadium to titanium is 1:(0.01-50); and / or The mass ratio of the co-catalytic component A to vanadium is (0.001-0.5):1; and / or The mass ratio of the co-catalytic component B to vanadium is (0.001-0.5):

1.

6. The preparation method according to claim 5, wherein, The mass ratio of vanadium to titanium is 1:(0.08-20); and / or The mass ratio of the co-catalytic component A to vanadium is (0.005-0.1):1; and / or The mass ratio of the co-catalytic component B to vanadium is (0.005-0.1):

1.

7. The preparation method according to claim 1, wherein, The mass ratio of the active component to the carrier, based on oxides, is 1:(1-50).

8. The preparation method according to claim 7, wherein, The mass ratio of the active component to the carrier, based on oxides, is 1:(4-25).

9. The preparation method according to claim 1, wherein, The mass ratio of titanium oxide to titanium precursor is (0.01-10):1, based on the mass of titanium oxide provided. And / or, The conditions for mixed contact include: temperature of 20-150℃; time of 0.5-5h; pH of 0.5-3; and / or The mass ratio of the titanium source to the solvent is (0.001-100):

1.

10. The preparation method according to claim 1, wherein, The conditions for mixed contact include: temperature of 30-90℃; time of 0.5-5h; pH of 0.5-3; and / or The mass ratio of the titanium source to the organic modifier is (0.01-10):1; and / or The mass ratio of the titanium source to the solvent is (0.01-10):

1.

11. The preparation method according to claim 1, wherein, The content of anatase titanium oxide in the titanium oxide is greater than or equal to 90 wt%.

12. The preparation method according to claim 1, wherein, The solvent includes one or more of C1-C4 alcohols, polyethanolamines, and water.

13. The preparation method according to claim 1, wherein, The solvent includes one or more of ethanol, triethanolamine, and water.

14. The preparation method according to claim 1, wherein, The organic modifier is one or more of dodecylamine, hexadecyltrimethylammonium bromide, and triblock copolymer P123.

15. The preparation method according to claim 14, wherein, The organic modifier is a mixture of triblock copolymer P123 and hexadecyltrimethylammonium bromide.

16. The preparation method according to claim 15, wherein, The mass ratio of triblock copolymer P123 to hexadecyltrimethylammonium bromide is (0.01-10):

1.

17. The preparation method according to claim 1, wherein, The preparation of a solution containing an active element source for oxidation includes: mixing and contacting the main catalytic active element source and the reducing agent in an aqueous solution to obtain a mixed solution, and then adding a co-catalytic active element source and mixing.

18. The preparation method according to claim 17, wherein, The mass ratio of the main catalytic active element source to the reducing agent is (0.001-10):1; and / or The main catalytic active element source includes a vanadium source; and / or The reducing agent includes one or more of formic acid, oxalic acid, citric acid, and L-ascorbic acid; And / or, The contact method between the solution containing the active source and the carrier is either spraying or dipping.

19. The preparation method according to claim 18, wherein, When using the spraying method, the spraying conditions include: a spraying temperature of 80-200℃; When using the impregnation method, the impregnation conditions include an impregnation temperature of 80-200℃.

20. The preparation method according to claim 19, wherein, When using the spraying method, the spraying conditions include: a spraying temperature of 100-150℃; When using the impregnation method, the impregnation conditions include an impregnation temperature of 80-150℃.

21. The use of the catalyst obtained by the preparation method according to any one of claims 1-20 in the oxidation reaction of methyl-containing aromatic hydrocarbons.

22. The application according to claim 21, wherein, The methyl-containing aromatic hydrocarbon is selected from one or more of toluene, o-xylene, mesitylene, methylnaphthalene, 2,3-dimethylnaphthalene, and 2,3,6,7-tetramethylnaphthalene.

23. A method for the gas-phase oxidation of mesitylene, characterized in that, The method comprises reacting mesitylene, air and the catalyst obtained by the preparation method according to any one of claims 1-20 in a gas-phase oxidation environment.

24. The method according to claim 23, wherein, Reaction conditions include: reaction temperature 330-500℃; and / or Volumetric hourly space velocity is 2000-10000 h. -1 ; The mass concentration of mesitylene is 13-60 g / m³. 3 .

Citation Information

Patent Citations

  • Catalyst used in a process for producing pyromellitic dianhydride

    US5001100A

  • Catalyst for preparing pyromellitic dianhydride by oxidizing durene as well as preparation method and application of catalyst

    CN112536025A